2008
DOI: 10.1186/1471-213x-8-81
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Groucho/TLE proteins during pancreas development

Abstract: Background: The full-length mammalian homologs of groucho, Tle1, 2, 3, and 4, act as transcriptional corepressors and are recruited by transcription factors containing an eh1 or WRPW/Y domain. Many transcription factors critical to pancreas development contain a Gro/TLE interaction domain and several have been shown to require Gro/TLE interactions for proper function during neuronal development. However, a detailed analysis of the expression patterns of the Gro/TLE proteins in pancreas development has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 56 publications
2
32
0
Order By: Relevance
“…In the pancreas, Grg2 and Grg3 are coexpressed with Nkx2.2 Hoffman et al 2008), and Grg3 interacts with Nkx2.2 via the conserved TN domain ). To determine whether the physical interaction between Nkx2.2 and Grg proteins is necessary for appropriate pancreatic islet development and/or function, we generated mice that express a mutant allele of Nkx2.2 containing amino acid substitutions within the core sequence of the TN domain (Nkx2.2 TNmut/TNmut ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the pancreas, Grg2 and Grg3 are coexpressed with Nkx2.2 Hoffman et al 2008), and Grg3 interacts with Nkx2.2 via the conserved TN domain ). To determine whether the physical interaction between Nkx2.2 and Grg proteins is necessary for appropriate pancreatic islet development and/or function, we generated mice that express a mutant allele of Nkx2.2 containing amino acid substitutions within the core sequence of the TN domain (Nkx2.2 TNmut/TNmut ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of Nkx2.2 to act as a transcriptional repressor in the developing pancreas has also been shown ). Grg2 and Grg3, rather than Grg4, are coexpressed with Nkx2.2 in the pancreas and can also interact with Nkx2.2 through the groucho interaction TN domain Hoffman et al 2008). In this study, we mutated the Nkx2.2 TN domain to determine the role of Grg-mediated Nkx2.2 repressor activity in the developing pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Arx overexpression in Activin A-treated a-cells prevents the reduction to cell proliferation but not the repression of Gcg expression in pancreatic a-cells [Mamin and Philippe, 2007]. Another study has examined the interaction of Groucho/Tle transcriptional corepressors with transcription factors important in the endocrine pancreas [Hoffman et al, 2008]. This study proposes roles for Groucho/Tle corepressors acting upon many transcription factors involved in endocrine pancreas development, including Neurog3.…”
Section: Arx Function In the Endocrine Pancreasmentioning
confidence: 99%
“…This study proposes roles for Groucho/Tle corepressors acting upon many transcription factors involved in endocrine pancreas development, including Neurog3. In particular, Tle2 was shown to interact with Arx and in b-cells this corepressor modulates the repressive capacity of Arx transcriptional activity [Hoffman et al, 2008].…”
Section: Arx Function In the Endocrine Pancreasmentioning
confidence: 99%
“…Grg3 was found to repress liver genes such as albumin in the endoderm, restraining liver specification until the Grg3 protein was extinguished. Conversely, Grg3 is highly expressed in the pancreas during embryonic development (Doyle et al, 2007;Hoffman et al, 2008). RNA in situ analysis in the pancreas demonstrated that Grg3 is expressed at much higher levels than other Grg family members, Grg1, Grg2 and Grg4 (Doyle et al, 2007).…”
Section: Introductionmentioning
confidence: 99%